IMPLEMENTASI ANGGARAN BERBASIS KINERJA DI INDONESIA - Kuntaryanto, Oki (KIAT BISNIS, 2013)
Performance based budgeting is an answer to old style budgeting which is traditionalbudgeting. Due to its benefits, many countries implement this kind of budgeting system.Indonesia is also a country which tries to implement this budgeting system as areplacement for traditional budgeting. However, the implementation of budgeting systemcreates several controversies. This article tries to investigate the implementation ofperformance based budgeting in Indonesia. By using literature study, this articleinvestigates the implementation of performance based budgeting in several public entitiesin Indonesia, both central government entities and local government entity. The entities tobe investigated are: Sekretariat Negara (State Secretariat), Direktorat JenderalPerbendaharaan Negara (State Treasurer), Kabupaten Tanah Datar (The Regency ofTanah Datar), central government entities, and state university. The results imply thatimplementation of performance based budgeting still experiences some constraints whichare typical. The first constraint is the problem how to link between funding andperformance indicator which most entities put focus too much on the link between them.The second constraint comes from the involvement of parliament which is too focus onpolitical vested interest. The third constraint lies on the limitation of human resource.Keywords: performance based budgeting, perormance, budgeting, government, indicator